Optimization of Supercritical CO2 Extraction of Essential Oil from Neem Leaves Using Response Surface Methodology - Lee , Pei Ting (IRC, 2016)
Neem tree with the scientific name Azadiractha indica, is a tree full of medicinal uses. Every part of the tree has its own biological activity which could aid in fighting and curing diseases. Extraction of the essential oil was carried out on neem leaves which are abundance throughout the whole year. The aim of this study is to optimize parameters of supercritical carbon dioxide extraction of neem leaves. The experiments were conducted in a continuous supercritical CO2 extractor at temperatures of 302.82 - 333.18 K, pressures of 6.69 - 29.31 MPa, and neem particles sizes of 0.06 - 0.75 mm.